Trehalose as an important energy source for immune cells in Drosophila melanogaster - Lehr, Katharina (Jihočeská univerzita, 2019)
The aim of this thesis was the identification of the change of trehalase gene expression in hemocytes of Drosophila melanogaster in uninfected and infected larvae using parasitoid wasp infection by Leptopilina boulardi. Moreover, the energy supply was shut down by deactivating the trehalose transporter and measuring the lamellocyte production, again in uninfected and infected larva to test the role of trehalose for the selfish immune system.
Trehalose as an important energy source for immune cells in Drosophila melanogaster